Outcome Evaluation of the work of the CGIAR Research Program on Water, Land and Ecosystems (WLE) on soil and water management in Ethiopia - Douthwaite, Boru; Getnet , K. (CGIAR Research Program on Water, Land and Ecosystems, 2019)
In 2019, the CGIAR Research Program on Water, Land and Ecosystems (WLE) Leadership chose to evaluate WLE’s work in Ethiopia as one of its countries where it has had most success. The objectives of the evaluation are: To determine how and in what ways WLE contributed to the achievement of intended/unintended outcomes; Based on the findings of the evaluation, make recommendations of how WLE (and its partners) can become more effective in supporting soil and water management in Ethiopia; To serve as a participatory learning experience for WLE and its partners. This report describes the evaluation process, findings, conclusions and recommendations.